Comorbidities in patients with gout in rheumatology clinic Dr. Hasan Sadikin general hospital in 2012 - 2013 - Limanjaya, W R; Wachjudi, Rachmat Gunadi; Tansah, H (Indonesian Journal of Rheumatology, 2016)
Background: Gout is a metabolic disease manifested mainly as an intense monoarticular inflammatory reaction which is strongly associated with hyperuricemia. Latest evidence showed that uric acid exerted effects on the development of other diseases. Many studies in developed countries had estimated the frequency of comorbidities associated with gout suchas hypertension, obesity, diabetes mellitus, Chronic Kidney Disease (CKD), and Myocardial Infarct (MCI). However, no data regarding these frequencies have been found in Indonesia up to now to the best of the authorâs knowledge. This study aimed to establish thefrequency of these comorbidities in patients with gout in Rheumatology Clinic Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.Methods: All medical records of patients with gout in Rheumatology Clinic Dr. Hasan Sadikin General Hospital from January 2012 to December 2013 were collected. The data on blood pressure; Body Mass Index (BMI); random blood glucose, fasting blood glucose or 2 hourspost prandial blood glucose; history of myocardial infarction; and creatinine were taken and analyzed to determine the presence of comorbiditiesÂ Results: Among all patients with gout in Rheumatology Clinic Dr. Hasan Sadikin General Hospital, 53.08% had chronic kidney disease, 42.73Â % had hypertension, 25.39% had diabetes mellitus, 15.70% had myocardial infarction and 12.22% had obesity.Conclusions: Comorbidities commonly found in patients with gout in order of frequency were chronic kidney disease, hypertension, diabetes mellitus, myocardial infarct, and obesity.Keywords: gout, comorbidities, frequency.